Research on parameters optimization of bilateral ring gear blank-holder in thick-plate fine blanking - C.J.Su; X.H.Dong; S.M.Guo; Q.L.Li; T.T.Li (Fracture and Structural Integrity)
To compensate for the poor quality of thick-plate blanking parts in cross-section, this paper suggests using the optimizing bilateral ring gear holder parameters to increase burnish zone and improve cutting precision. With the bilateral gear ring, the hydrostatic pressure of shear deformation zone will increase, plasticity of the material will be lifted to maximum and quality of the cross section will be raised. This paper establishes 8mm AISI-1020 fine blanking model by DEFORM2D, analysis different ring gear parameters and clearance that are influenced the stress-strain and cross section quality to predict forming defects. By using the bilateral gear ring blank holder, the poor quality of thick-plate blanking section is successfully enhanced. Therefore, the bilateral gear ring blank holder is vital to improve the quality of blanking parts and provide the reliable theory basis for the practical engineering application.